Offshoring under Uncertainty - Wilhelm Kohler; Bohdan Kukharskyy (Center for Economic Studies and ifo Institute (CESifo), 2018)
We develop a theoretical framework to explain firms' offshoring decisions in the presence of uncertainty. This model highlights the role of labor market institutions in shaping a firm's ability to effectively react upon future shocks, yielding a sharp prediction of the prevalence of offshoring in a given industry: The propensity of firms to source intermediate inputs from foreign rather than domestic suppliers decreases in a foreign country's labor market rigidity, and this effect is particularly pronounced in industries with higher volatility. Combining industry-level data on the U.S. offshoring intensity with measures of labor market rigidity and industry volatility, we find empirical evidence strongly supportive of the model's predictions.
Keywords: F14; F16; F23; 330; offshoring; uncertainty; labor market rigidity; industry volatility